Redefining the Concept of Advertising in Romanian: Between Need and Reality - Șimon, Simona (Technium Social Sciences Journal, 2020)
Advertising is an undisputed reality of the contemporary world, being a form of communication present both in and beyond mass media. With the evolution of the society, new means of expression have emerged and determined an expansion of the range of advertising products offered for information, persuasion and, why not, for enjoyment. However, as advertising expanded its scope, the meanings attributed to the concept began to change and broaden at the same time. In the Romanian cultural space, this evolution of the concept, as well as the increasing presence of English in all instances of communication have led to a dynamisation of the process of defining advertising, especially due to the new meanings revealed by the definition of the concept in English. In this context, the present article aims to highlight the existence of some discrepancies between the definition of the concept and the terminology already established in Romanian, on the one hand, and to offer solutions that smooth the way to a better equivalence of the meanings assigned to the concept in the process of translating it from Romanian into English, on the other hand. Considering the problem statement, our own observations and the data collected from the online survey carried out among the students pursuing a bachelor’s degree at the Faculty of Communication Sciences, two definitions of the Romanian concepts of publicitate and reclam? are put forth in order to bridge the conceptual gap existing in the Romanian cultural space.